2021
DOI: 10.47540/ijsei.v2i2.256
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Ecology of Epiphytic & Terrestrial Orchids in Langchenphu, Jomotsangkha Wildlife Sanctuary, Bhutan

Abstract: Orchids are the largest and diverse families of flowering plants. Orchids are found growing mostly in tropical climates affecting various communities socio-economically. Among many protected areas in Bhutan, Jomotshangkha Wildlife Sanctuary (JWS) is the least explored in terms of flora and fauna. The study was carried out to assess diversity, host tree preferences and to determine the growth zone of epiphytic orchids along the altitudinal gradient in Langchenphu gewog in JWS. Transect technique was used in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Epiphytic orchids generally attach to parts of the tree that are exposed to direct sunlight with temperatures, humidity, and nutrients that are following the orchid's physiology (Baiduri & Fitriani, 2019). Some types of orchids can only live on certain trees (Choden et al, 2021), so the presence of trees (hosts) for orchids will also strongly affect the diversity of orchid species in ecosystem. The data above shows that the 4 epiphytic orchid species found are in 33-49 masl altitude range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epiphytic orchids generally attach to parts of the tree that are exposed to direct sunlight with temperatures, humidity, and nutrients that are following the orchid's physiology (Baiduri & Fitriani, 2019). Some types of orchids can only live on certain trees (Choden et al, 2021), so the presence of trees (hosts) for orchids will also strongly affect the diversity of orchid species in ecosystem. The data above shows that the 4 epiphytic orchid species found are in 33-49 masl altitude range.…”
Section: Resultsmentioning
confidence: 99%
“…Altitude is one of the main factors affecting the distribution of epiphytic orchids. Choden et al, (2021) reported that the diversity of epiphytic orchids in the lowlands was much less because the area was mostly covered by settlements and had less vegetation cover. This is in accordance with the location of the forest in the orchid garden area which is not far from the beach or at a low-medium altitude.…”
Section: Resultsmentioning
confidence: 99%